Leading Indicators of Turkey’s Financial Crises - Kaakeh, Mohamad (Eastern Mediterranean University EMU - Doğu Akdeniz Üniversitesi (DAÜ), 2017)
This study empirically observes the leading indicators of 1994, 2000/2001 and 2009 Turkish financial crises. Stepwise regression, Probit and Logit models have been applied to three sets of quarterly data covering the periods of Q1-1990 to Q4- 1999 to investigate the leading indicators of the 1994 crisis, from Q3-1996 to Q2-2005 to capture the 2000/2001 twin crises, and from Q3-2005 to Q3-2015 to see the global financial crisis effect on Turkey. Results assert that the three crises of Turkey are different in structure and each has different characteristics with different leading indicators. The results provide a new set of leading indicators that includes capital adequacy and long-term interest rates as well as international variables, and these indicators are compatible with the new structure of Turkish economy. Regulators and policymakers should pay close attention to macroeconomic variables and the banking sector stability of Turkey as well as the status of the global economy as the results show that many banking and international related variables increase the probability of the crisis, this can be through imposing tighter regulations on banks to avoid default and credit risk, following the liquidity levels in the markets and closely following the stability of global economic indicators. Keywords: Financial crisis, Turkey, stepwise regression, probit and logit models, leading indicators.

ÖZ: Bu çalışmada, 1994, 2000/2001 ve 2009 Türkiye finansal krizlerinin öncü göstergeleri Stepwise regresyon, Probit ve Logit tahmin yöntemleri kullanılarak ampirik olarak incelenmiştir. 1990-2015 yıllarını kapsayan çeyreklik veri seti her bir krizin öncü göstergelerinin tespit edilebilmesi amacıyla 1990-1999, 1996-2005, 2005-2015 olmak üzere üç alt gruba ayrılmıştır. Sonuçlar, Türkiye’de yaşanan her üç krizin de birbirinden yapısal olarak belirli ölçüde farklı olduğunu göstermiş ve her bir kriz için elde edilen öncü göstergelerde farklılıklar olduğu görülmüştür. Çalışma sermaye yeterliliği, uzun vadeli faiz oranları ile uluslararası değişkenleri içeren ve Türk ekonomisinin değişen yapısıyla uyumlu yeni bir öncü göstergeler seti önermektedir. Bulgular bankacılık sektörü ile ilgili çeşitli değişkenlerin yanında, ülke dışında yaşanan olumsuz gelişmelerin de ülkede bir kriz yaşanma ihtimalini artırdığını göstermektedir. Elde edilen sonuçlar politika yapıcıların ve düzenleyici organların ülkenin temel makroekonomik göstergeleri yanında, küresel ekonomideki gelişmeleri de yakından takip etmelerinin ve bankacılık sektöründe istikrarın sağlanmasının önemine işaret etmektedir. Uygulanabilecek önlemler arasında piyasalardaki likidite seviyesinin kontrol altında tutulması, kredi riskini azaltabilmek için bankaların gözetim-denetimine önem verilmesi ve küresel ekonomik şoklara karşı alınacak önlemlerin planlanması sayılabilir. Anahtar Kelimeler: Finansal kriz, Türkiye, stepwise regresyonu, probit ve legit modelleri, öncü göstergeler.
Master of Science in Banking and Finance. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Banking and Finance, 2017. Supervisor: Assoc. Prof. Dr. Korhan K. Gökmenoğlu.
Keywords: Banking and Finance; Economic conditions and development-Turkey; Financial Crises-Turkish Economy; Financial crisis; Turkey; stepwise regression; probit and logit models; leading indicators